2005
DOI: 10.1021/jf052137k
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Antioxidants (Hydrolyzable Tannins, Flavonols, and Anthocyanins) Identified by LC-ESI-MS and MALDI-QIT-TOF MS from Rosa chinensis Flowers

Abstract: Rosa chinensis (Yuejihua) is a well-known ornamental plant, and its flowers are commonly used in traditional Chinese medicine. Methanolic crude extracts of dried R. chinensis flowers were used for simultaneous determination of phenolic constituents by liquid chromatography-mass spectrometry (LC-MS) and matrix-assisted laser desorption/ionization quadrupole ion trap time-of-flight mass spectrometry (MALDI-QIT-TOF MS). A total of 36 known and unknown phenolics were identified as hydrolyzable tannins, flavonols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 32 publications
(68 reference statements)
7
97
0
1
Order By: Relevance
“…Compounds 2, 5, 10, 12, 14 performing maximum UV absorbance in the range of 255-280 nm, was in agreement with the identification of hydrolysable tannin from Rosa chinensis flowers (Cai, Xing, Sun, Zhan, & Corke, 2005). Compound 5 could be pendunculagin (Bis-2, 3; 4, 6-O-hexahydroxydiphenoylglucose) with [M-H] − ion at m/z 783 consisted of two HHDP (Hexahydroxydiphenoyl) groups (302 unit per group) and one glucosyl group (180 unit) (Tian, Li, Ji, Zhang, & Luo, 2009;Salminen, Ossipov, Loponen, Haukioja, & Pihlaja, 1999) Table 2.…”
Section: Hydrolysable Tanninsupporting
confidence: 85%
“…Compounds 2, 5, 10, 12, 14 performing maximum UV absorbance in the range of 255-280 nm, was in agreement with the identification of hydrolysable tannin from Rosa chinensis flowers (Cai, Xing, Sun, Zhan, & Corke, 2005). Compound 5 could be pendunculagin (Bis-2, 3; 4, 6-O-hexahydroxydiphenoylglucose) with [M-H] − ion at m/z 783 consisted of two HHDP (Hexahydroxydiphenoyl) groups (302 unit per group) and one glucosyl group (180 unit) (Tian, Li, Ji, Zhang, & Luo, 2009;Salminen, Ossipov, Loponen, Haukioja, & Pihlaja, 1999) Table 2.…”
Section: Hydrolysable Tanninsupporting
confidence: 85%
“…Similarly, peaks 46 and 48 were tentatively identified as a kaempherol hexoside and a quercetin-O-pentoside, respectively. The MS 3 analysis of peak 46 showed that deprotonated base ion of the glycoside at m/z 447 with maximum absorbance at 255 and 350 nm and the ion at m/z 285 corresponding to the deprotonated aglycone of kaempherol (Cai, Xing, Sun, Zhan, & Corke, 2005). Since glucose is the most common sugar present, peak 46 was suggested to be kaempherol 3-O-glucoside (Cuyckens & Claeys, 2004).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Flavonols in the crude extract of the dried Rose chinensis flowers have been identified by MALDI-TOF MS without using any matrix [30]. Recently, flavonoids -quercetin and rutin -have been used as new matrices for MALDI-TOF-MS analysis of Pt(II) and Pd(II) complexes [31].…”
Section: Introductionmentioning
confidence: 99%